DFT Study of Electronic and Optical Properties of Small Oligothiophenes Based on Terthiophene End-capped by Several Donor Groups - Aziz El Alamy; Amina Amine; Mohammed Bouachrine (Orbital: The Electronic Journal of Chemistry, 2017)
Eight small molecules based on terthiophene end-capped by several donor groups have been carried out using density functional theory (DFT) and time-dependent (TDDFT) methods in neutral and doped states. The theoretical ground-state geometry, electronic structure and optical properties of the studied molecules were obtained by the DFT and TD-DFT methods at the B3LYP level with 6-31G(d) basis set. Theoretical knowledge of the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) energy levels the gap energy (Eg) and the open-circuit voltage (Voc) of the studied compounds are calculated and discussed. The effects of the donor group substituents on the geometries and optoelectronic properties of these materials are discussed to investigate the relationship between molecular structure and optoelectronic properties. The results of this work suggest some of these materials as a good candidate for organic solar cells.DOI: http://dx.doi.org/10.17807/orbital.v9i3.995